Targeting Strategies for Glucose Metabolic Pathways and T Cells in Colorectal Cancer - Wang, Gang; Wang, Jun-Jie; Guan, Rui; Sun, Yan; Shi, Feng; Gao, Jing; Fu, Xing-Li (Current Cancer Drug Targets, 2019)
Colorectal cancer is a heterogeneous group of diseases that result from the accumulation of different sets of genomic alterations, together with epigenomic alterations, and it is influenced by tumor–host interactions, leading to tumor cell growth and glycolytic imbalances. This review summarizes recent findings that involve multiple signaling molecules and downstream genes in the dysregulated glycolytic pathway. This paper further discusses the role of the dysregulated glycolytic pathway in the tumor initiation, progression and the concomitant systemic immunosuppression commonly observed in colorectal cancer patients. Moreover, the relationship between colorectal cancer cells and T cells, especially CD8+ T cells, is discussed, while different aspects of metabolic pathway regulation in cancer cell proliferation are comprehensively defined. Furthermore, this study elaborates on metabolism in colorectal cancer, specifically key metabolic modulators together with regulators, glycolytic enzymes, and glucose deprivation induced by tumor cells and how they inhibit T-cell glycolysis and immunogenic functions. Moreover, metabolic pathways that are integral to T cell function, differentiation, and activation are described. Selective metabolic inhibitors or immunemodulation agents targeting these pathways may be clinically useful to increase effector T cell responses for colorectal cancer treatment. However, there is a need to identify specific antigens using a cancer patient-personalized approach and combination strategies with other therapeutic agents to effectively target tumor metabolic pathways.
Keywords: T cells